2007
DOI: 10.1063/1.2786837
|View full text |Cite
|
Sign up to set email alerts
|

Photoemission study of the electronic structures of tris-(8-hydroxyquinoline) aluminum/Li2O∕Al interfaces

Abstract: The electronic structures of tris-(8-hydroquinoline) aluminum (Alq3)∕Li2O∕Al interfaces were studied using in situ ultraviolet and x-ray photoelectron spectroscopies (UPS and XPS). The UPS and XPS spectra allowed us to evaluate the complete energy level diagrams and to analyze the chemical interactions at the interfaces. Inserting Li2O between Al and Alq3 led to the highest occupied molecular orbital (HOMO) of Alq3 shifting to a higher binding energy compared to that without Li2O, which resulted in an improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The higher brightness is attributed to the improved electron injection of electron and more balanced recombination of electrons and holes. The peak efficiency for LiBH 4 device was also about 10% higher the LiF device as shown in Fig. 1(c).…”
Section: Devices With Libh 4 Eilmentioning
confidence: 74%
See 1 more Smart Citation
“…The higher brightness is attributed to the improved electron injection of electron and more balanced recombination of electrons and holes. The peak efficiency for LiBH 4 device was also about 10% higher the LiF device as shown in Fig. 1(c).…”
Section: Devices With Libh 4 Eilmentioning
confidence: 74%
“…1(a), the IV curve of the LiBH 4 based device has a steeper rise than the control device with LiF/Al cathode. At 10V, the current densities were 6089 A/m 2 and 3556 A/m 2 for LiBH 4 and LiF device, respectively. The LiBH 4 based device also showed higher brightness at the same driving voltage.…”
Section: Devices With Libh 4 Eilmentioning
confidence: 99%
“…15 In addition, we also performed in situ PES experiments to check if both lithium oxides, which are formed from the source of Li 2 O and LiCoO 2 , show identical electronic structures. Actually, they show identical electronic structures and the strong dipole on ITO substrate (not shown here because the electronic structures of Li 2 O are already well known 15,16 ). Therefore, we expect the same result if we use Li 2 O itself as the source of lithium oxide instead of LiCoO 2 .…”
mentioning
confidence: 73%
“…With the strong chemical interaction between Alq 3 and alkali metals, a significant gap state emerges, which could deteriorate the device stability. [16][17][18] However, the gap state was hardly seen at the interface of Li 2 O/Alq 3 . Therefore, this weak interaction between Li 2 O and Alq 3 would also contribute to the extension of the device lifetime as well as the eD formation.…”
mentioning
confidence: 99%
“…30 This lifetime increase is attributed to the fact that during deposition there is LiCoO 2 decomposition and formation of LiO, which has been reported to reduce the destructive interaction between the cathode and Alq 3 . 31 In the case of OPVs, similar lifetime improvement was obtained by substituting CsCO 3 with LiF, which delayed oxygen contamination of the organic materials. 32 It is concluded that oxides, such as LiO, CsCO 3 , etc., allow for the improvement of the lifetime of the devices.…”
Section: Resultsmentioning
confidence: 99%